Perception Of Educators Towards Mobile Learning - Zulkafly, Nor Alley (2011)
This study explores the perception of educators on mobile learning. Educators play an important role as key player to produce materials especially notes and updates. It seems that students were more confident and positive towards mobile learning compared to the educators who were reviewed as conservative in terms of knowledge and skills. Besides, the educators were passive towards adopting mobile learning. The change in education technologies begin with the perception of educators toward the technologies.